Ethnicity In Khaled Hosseini's Novels (The Kite Runner, A Thousand Splendid Suns, Andand The Mountain Echoed): A Sociological Approach - Pertiwi, Dian Ratna; , Dr. M. Thoyibi, M.S (2016)
This study is about ethnicity in Khaled Hosseini's novels entitled The Kite Runner, A Thousand Splendid Suns, and And The Mountain Echoed. The novels are analyzed by using Sociological approach. The objectives of this study are to find out the ethnic identity in ethnicity, the types of ethnic, and the researcher concerns about ethnicity in society especially in Afghanistan. This research belongs to qualitative research. The primary data of this study are The Kite Runner, A Thousand Splendid Suns and And The Mountain Echoed by Khaled Hosseini novels. The secondary data of this study are taken from literary books, virtual sources and other sources that related to the issue of ethnicity. This study comes to conclusions as follows; first, four indicators indicate ethnic identity, the language, the religion, the physical traits and the fashion style. Second, the types of ethnicity is described in four types, primary and secondary ethnic group, the folk-community and nationality-community ethnic group, the majority and minority ethnic group, also the young and old ethnic group. Third, Khaled Hosseini has a concern for the suffering of Afghan people. He concerns about the oppression based on ethnicity, race or gender. Hosseini shows his hand to the minority ethnic group in Afghanistan, he gives the critique of the war that never ended, poverty and famine because of war caused death. He wants to promote gender and ethnic equality in Afghanistan.